Laser Processing of Transparent Wafers with a AlGaN/GaN Heterostructures and High-Electron Mobility Devices on a Backside - Simonas Indrišiūnas; Evaldas Svirplys; Justinas Jorudas; Irmantas Kašalynas (Micromachines, 2021)
Sapphire and silicon carbide substrates are used for growth of the III-N group heterostructures to obtain the electronic devices for high power and high frequency applications. Laser micromachining of deep channels in the frontside of the transparent wafers followed by mechanical cleavage along the ablated trench is a useful method for partitioning of such substrates after the development of the electronics on a backside. However, in some cases damage to the component performance occurs. Therefore, the influence of various parameters of the laser processing, such as fluence in the spot size, substrate thickness, orientation, and the polarization of focused laser beam, to the formation of damage zones at both sides of the transparent substrate with thin coatings when ablating the trenches from one side was investigated. The vicinity effect of the ablated trenches on the performance of the electronics was also evaluated, confirming the laser micromachining suitability for the dicing of transparent wafers with high accuracy and flexibility.